Three‐dimensional brain MRI for DBS patients within ultra‐low radiofrequency power limits. Issue 4 (17th January 2014) - Sarkar, Subhendra N.; Papavassiliou, Efstathios; Hackney, David B.; Alsop, David C.; Shih, Ludy C.; Madhuranthakam, Ananth J.; Busse, Reed F.; La, Susan; Bhadelia, Rafeeque A.
ABSTRACT Background For patients with deep brain stimulators (DBS), local absorbed radiofrequency (RF) power is unknown and is much higher than what the system estimates. We developed a comprehensive, high‐quality brain magnetic resonance imaging (MRI) protocol for DBS patients utilizing three‐dimensional (3D) magnetic resonance sequences at very low RF power. Methods Six patients with DBS were imaged (10 sessions) using a transmit/receive head coil at 1.5 Tesla with modified 3D sequences within ultra‐low specific absorption rate (SAR) limits (0.1 W/kg) using T2, fast fluid‐attenuated inversion recovery (FLAIR) and T1‐weighted image contrast. Tissue signal and tissue contrast from the low‐SAR images were subjectively and objectively compared with routine clinical images of six age‐matched controls. Results Low‐SAR images of DBS patients demonstrated tissue contrast comparable to high‐SAR images and were of diagnostic quality except for slightly reduced signal. Conclusions Although preliminary, we demonstrated diagnostic quality brain MRI with optimized, volumetric sequences in DBS patients within very conservative RF safety guidelines offering a greater safety margin. © 2014 International Parkinson and Movement Disorder Society